Public Vows : Fictions of Marriage in the English Enlightenment - Ganz, Melissa J., 1972- (Book collections on Project MUSE., 2019)
In eighteenth-century England, the institution of marriage became the subject of heated debates, as clerics, jurists, legislators, philosophers, and social observers began rethinking its contractual foundation. Public Vows argues that these debates shaped English fiction in crucial and previously unrecognised ways and that novels, in turn, played a central role in the debates.